A INGESTÃO DIETÉTICA DE VITAMINA K ESTÁ ASSOCIADA A PARÂMETROS DE OBESIDADE ENTRE ADOLESCENTES? - Elizabete Alexandre dos Santos; Kelly Virecoulon Giudici; Nastasha Aparecida Grande de França; Barbara Santarosa Emo Peters; Regina Mara Fisberg; Lígia Araújo Martini (Universidade do Estado do Rio de Janeiro, 2019)
Background: Adolescence is a phase with many changes in body composition, so the investigation of the ingestion of micronutrients like vitamin K becomes important, as it may be indirectly related to obesity among these individuals. Thus, this study aimed to investigate the relationship between vitamin K intake, nutritional status and serum levels of osteocalcin, leptin and adiponectin among adolescents. Methodology: Cross-sectional study conducted with 129 adolescents of both sexes, aged 14 to 18 years, participants in the São Paulo Municipal Health Survey 2008 (ISA-Capital 2008). Peripheral venous blood was collected to determine: serum intact total osteocalcin (tOC), undercarboxylated osteocalcin (ucOC), leptin and adiponectin. Spearman's correlation and multiple linear regression were performed to evaluate the associations between vitamin K intake and anthropometric and biochemical variables. Results: In normal weight subjects, vitamin K intake had a positive correlation with age (r= 0.2489; p= 0.0174) and a negative correlation with weight (r= -0.2335; p= 0.0259). In the total sample, vitamin K intake did not correlate with weight (r = -0.0856, p= 0.3442), BMI (r = 0.0669, p = 0.4621), leptin (r= 0.1291, p = 0.1530), adiponectin (r = -0.0682, p = 0.4517), tOC (r = 0.0442, p = 0.6256) and ucOC (r = -0.1136, p = 0.2110). Conclusions: A negative correlation between vitamin K intake and body weight was observed in normal weight subjects. The metabolic pathways involved in the relation between vitamin K intake and body composition remain unclear. DOI: 10.12957/demetra.2019.39079